Interactive Effects of Grafting Time and Technique on the Sprouting Time and Growth of Guava Grafts (Psidium guajava L.) - arjoo; Sharma, Sushil; Rajat; Aayush; Vikalp (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during June to September, 2021 at the experimental orchard of the Department of Horticulture, CCS Haryana Agricultural University, Haryana, India to investigate the impact of propagation methods, time, and varieties on the success rate of guava (Psidium guajava L.) propagation. The treatments were arranged in a three factorial layout using a Randomized Complete Design with three replications. In the months of June, July, August, and September, two different cultivars (L-49 and Hisar Safeda) and four different propagation techniques (Patch budding, T-budding, Wedge grafting, and Inarching) were applied six times each. The results revealed that wedge grafting exhibited the shortest time to sprout (14 days), whereas inarching displayed the longest duration for sprouting (54.33 days). The 2nd fortnight of July and the 1st fortnight of September demonstrated the most favorable time for bud sprouting. Moreover, Hisar Safeda exhibited superior performance compared to L-49 in terms of earlier sprouting and better growth. Therefore, propagation of guava using wedge grafting techniques during the months of July and September can be recommended for the study area and areas with similar agro-ecologies so as to achieve successful grafting within the shortest feasible timeframe. These findings offer crucial insights for agricultural practitioners seeking enhanced propagation techniques and optimal timings, thereby fostering improved guava cultivation practices and augmenting yields in similar agricultural settings.